(untitled) - Schumacher, E. F. (London, 1973)
This is a book that needs to make a comeback. Though written decades ago, it addresses how to build an economy that sustains the environment and isn't destructive to community. Most importantly to me, Schumacher makes the point that our model of economics is unsustainable because it is based on infinite growth and fails to distinguish between equity and capital. He also points out that economics is but one of many social science disciplines, and that on its own, economics is incapable of resolving any of the major problems we face, like maintaining the natural environment, building strong communities, promoting positive mental health, creating social justice, etc.
Keywords: Economics,Kinh tế học